[Sea Cave in Heimaey] - Streng, Evelyn Fiedler (1975)
Photograph of a sea cave in Heimaey. The triangular, shadowed cave sits in a brown cliff side ahead. Green and white streaks sit along the edges of the cliff throughout. The dark, shining ocean sits in the foreground past a blue item in the bottom left corner of the photograph.